Paralogii transformacii (post)modernistskogo diskursa v russkoj kulʹture 1920 - 2000-ch godov - Lipoveckij, Mark Naumovič 1964- (Novoe literaturnoe obozrenie, 2008)
Zsfassung in engl. Sprache u.d.T.: Paralogies: the transformations of (post)modernist discourse in Russian culture of the 1920s - 2000s